Graphic Interlude - Jay Hide; Melanie Friend; James McLaren (Angles)
This graphic interlude features a selection of photographs which can illustrate the adage ‘Brevity is the soul of wit’. True to the spirit of the adage, the viewer is invited to interpret the pictures which are presented without commentary.